2011
DOI: 10.4021/gr379w
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Interfere With Zinc Absorption and Zinc Body Stores

Abstract: BackgroundProton pump inhibitors (PPIs) cause a sharp elevation of gastro-duodenal luminal pH which in turn has resulted in reports of reduced absorption of magnesium and certain other nutrients.MethodsGastroesophageal reflux disease (GERD) patients on long-term PPI therapy (> 6 months) or healthy test subjects (not on any acid preventive or neutralizing medication) were administered oral doses of zinc gluconate (26.2 mg zinc, twice daily) for 14 days followed by 5 cc venous blood samples. Plasma was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 23 publications
2
35
0
1
Order By: Relevance
“…Therefore, patients with ESA-hyporesponsive anemia were not included in our study. It has also been reported that proton-pump inhibitors inhibit supplemental zinc absorption in non-uremic patients [ 20 ]. Because the subjects in the present study were all uremic patients and many of our patients had been treated with proton-pump inhibitors, the response to increased serum zinc levels and decreased ERI might be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with ESA-hyporesponsive anemia were not included in our study. It has also been reported that proton-pump inhibitors inhibit supplemental zinc absorption in non-uremic patients [ 20 ]. Because the subjects in the present study were all uremic patients and many of our patients had been treated with proton-pump inhibitors, the response to increased serum zinc levels and decreased ERI might be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is a zinc metalloprotease and chronic PPI use is known to reduce zinc levels in the body by depleting zinc stores as well as by preventing absorption of supplemental zinc [37]. The dose of PPI required to exert anti-SARS-CoV-2 effect has been estimated to be very high.…”
Section: Actions On Ace2mentioning
confidence: 99%
“…The Western world’s shift from consumption of meat proteins to cereal proteins containing high levels of fibers known as phyrates may reduce intestinal zinc absorption [29], [30]. Moreover, the very prevalent use of proton pump inhibitor medications may also create a state of zinc deficiency [31], which makes the issue of zinc deficiency in alcoholic patients more severe. However, the mechanism of how dietary zinc deficiency may impact alcohol-induced liver pathogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%